Around the world in 103 days - Scott, Peter (Wildfowl, 1957)
This account of our travels has been divided into a preliminary description of the whole journey followed by a more detailed description of the various species of Anatidae we encountered, told largely by direct quotation from diaries written at the time. For this Annual Report it seemed more appropriate to group these extracts from the diaries under the headings of the species concerned, which will also make them easier for reference than a chronological presentation.